Makna Bantuan Kemanusiaan Bagi Aktivis Perempuan - Syahrul Gunawan; Intan Nur Aziz; Dian Mulyani; Riska Yunisyah Imilda; Neni Yulianita (Jurnal Ilmiah Komunikasi (JIKOM) STIKOM IMA, 2023)
Various phenomena with the nuances of conflict that have caused thousands of victims have hit the eastern part of the world, such as what happened in Palestine and Syria, in addition to this, humanitarian violence has also occurred in Asian blocs, such as the Chinese Uighurs. Meanwhile, in the country itself, various natural disasters that occurred in Indonesia also felt victims. The occurrence of these various phenomena moved the hearts of women or known as activists so that they formed an organization, namely Golden Future, which took part in and helped victims of conflicts in the international sphere or victims of disasters that occurred in the national sphere. This study aims to find out the motives of Golden Future women activists in carrying out humanitarian aid activities, as well as knowing the meaning of humanitarian assistance for Golden Future women activists. The method used in this study is qualitative with a constructivism perspective and a phenomenological approach. The results of this study indicate that the first motive is the way to heaven according to Islamic law, the second motive is the realm of practicing knowledge, and the third is a driving force. And the meaning of humanitarian aid for women activists is to reach heaven, as the spearhead of civilization and a facility to awaken others.